Ghana Agriculture Production Survey (GAPS): 2011/2012 minor season Survey: Report on data quality and key indicators - Osei-Akoto, Isaac; Horlu, Godwin; Bonsu, Adwinmea; Appiah-Kubi, Wilson (International Food Policy Research Institute, 2014)
Since 1999, the Statistics, Research, and Information Directorate (SRID) of Ghana’s Ministry of Food and Agriculture (MoFA) has been collecting data and administering surveys using a Multi-Round Annual Crop and Livestock Survey (MRACLS) system to inform agricultural policy formulation and implementation. MRACLS provides information on agricultural production by giving estimates of field areas and yields of important crops. This method, however, does not provide detailed information about farmers, their practices, and the inputs they use, nor does it provide detailed information about local agricultural infrastructure. Therefore, an effort has been made to bridge the gap between agricultural data needs and data availability and quality.